2012
DOI: 10.1016/j.whi.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

“What My Doctor Didn't Tell Me”: Examining Health Care Provider Advice to Overweight and Obese Pregnant Women on Gestational Weight Gain and Physical Activity

Abstract: Background Appropriate gestational weight gain (GWG) is vital, as excessive GWG is strongly associated with postpartum weight retention and long-term obesity. How health care providers counsel overweight and obese pregnant women on appropriate GWG and physical activity remains largely unexplored. Methods We conducted semi-structured interviews with overweight and obese women following the birth of their first child to ascertain their experiences with GWG. A grounded theory approach was used to identify theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
135
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 17 publications
18
135
0
1
Order By: Relevance
“…Similar findings were made in a U.S. study of advice received by pregnant women regarding GWG. [48] It could be assumed that health professionals are overestimating or misremembering what they have discussed or might, as identified here, have "skirted around" the issue because of its sensitivity. Another explanation is that women had forgotten or misremembered the information given.…”
Section: Discussionmentioning
confidence: 96%
“…Similar findings were made in a U.S. study of advice received by pregnant women regarding GWG. [48] It could be assumed that health professionals are overestimating or misremembering what they have discussed or might, as identified here, have "skirted around" the issue because of its sensitivity. Another explanation is that women had forgotten or misremembered the information given.…”
Section: Discussionmentioning
confidence: 96%
“…The views and experiences of pregnant women with a raised BMI regarding health and weight have been explored in previous studies (Furber and McGowan 2010;Mills et al, 2011;Smith and Lavender 2011;Stengel et al, 2012;Heslehurst et al, 2013a); however, the views of couples have not previously been explored. Using qualitative methods, the complex histories and accounts that women provide for their weight have been accessed, including how individuals within a couple may experience and resist weight stigma together, or on behalf of a partner.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have shown that low quality is a problem on the Internet [10] and others have found that pregnant women may perceive advice from family physicians and midwives confusing, vague, contradictory and frequently changing [8,[11][12][13]. Also, research show that most health care providers, regardless of medical training, lack knowledge and awareness of the ACOG [6] PA guidelines [12,14], and the majority of pregnant women being counselled about weight gain report that the advice is generally discordant with the Institute of Medicine (IOM) [15] GWG guidelines [7,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Also, research show that most health care providers, regardless of medical training, lack knowledge and awareness of the ACOG [6] PA guidelines [12,14], and the majority of pregnant women being counselled about weight gain report that the advice is generally discordant with the Institute of Medicine (IOM) [15] GWG guidelines [7,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation